2018
DOI: 10.1007/s10980-018-0628-x
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic species as a cultural ecosystem service in the European Alps: insights and open issues

Abstract: Purpose Symbolic plants and animals are recognised as a cultural ecosystem service (CES), which is still underrepresented in ecosystem services assessments. Thus, this study aims at identifying and mapping important symbolic species in the European Alps, which are of cultural significance to large parts of the Alpine population. Methods Symbolic species were identified by ten expert groups, and their use was assessed in a qualitative way. The spatial distribution of all species across the Alpine Space area was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…Bears and wolf are indeed icons of wilderness (Tattoni et al 2017a) and their names are still a popular choice for hotels and restaurants, a recognised index of their cultural value (Schirpke et al 2018).…”
Section: Perception Of the Speciesmentioning
confidence: 99%
“…Bears and wolf are indeed icons of wilderness (Tattoni et al 2017a) and their names are still a popular choice for hotels and restaurants, a recognised index of their cultural value (Schirpke et al 2018).…”
Section: Perception Of the Speciesmentioning
confidence: 99%
“…Other approaches have used expert group evaluation to assess symbolic species for cultural services provision, for instance, in European Alps [9], with relevance because the human perceptions were considered. In the future, the combination of the two approaches might be a reasonable option for modeling cultural services through the habitat of iconic species.…”
Section: Habitat Suitability For the Iconic Species Iris Boissierimentioning
confidence: 99%
“…Mountains are often classified as protected areas, holding an essential role in the conservation of natural and cultural heritage and in the supply of ecosystem services. Tourism activities, especially those based on agro-tourism, eco-tourism, and wildlife (in particular symbolic species) in protected mountain areas, has been increasing in the last decades [9]. Several studies have shown that existing networks of protected areas supply considerable quantities of ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it can be assumed that large parts of the European Alps have a larger positive influence on the nexus with more ES, than only the water-related ones [27]. Alpine ecosystems play a significant part in the area and can, for example, positively influence cultural values also of the lowlands [48,67].…”
Section: Methodological Considerationsmentioning
confidence: 99%